Pay Gaps in the National Health Service: Observability and Disclosure - Karen A. Mumford; Edith Aguirre; Anna Einarsdóttir; Bridget Lockyer; Melisa Sayli; Benjamin A. Smith (Institute of Labor Economics (IZA), 2021)
Studies of the relationship between sexual orientation and pay have faced difficulties applying standard models of discrimination if orientation is not observable. Analogously, behavioural explanations of pay based on models of gender linked within-household specialization may not be as relevant in a nonheterosexual context. This article analyses pay gaps using information including earnings, gender, LGB identity, coupling status, and the disclosure of sexual orientation in English National Health Service (NHS) workplaces. The results reveal a robust gender pay gap of 4% in favour of males, but no overall LGB pay gap compared to heterosexuals. The latter is due to similar-sized offsetting effects from disclosure on LGB pay relative to comparable heterosexuals. Amongst LGB employees, disclosure is associated with 13% more pay, with three quarters of this gap related to unexplained differences in returns to observable characteristics. Supportive workplace practices are strongly associated with increased probability of disclosure, especially the availability of a LGB workplace network.
Keywords: J16; J31; J71; 330; disclosure; gender; LGB; NHS; pay